2016
DOI: 10.1002/jwmg.21464
|View full text |Cite
|
Sign up to set email alerts
|

Island fox spatial ecology and implications for management of disease

Abstract: Disease, predation, and genetic isolation resulted in 4 of 6 island fox (Urocyon littoralis) subspecies being listed as endangered in 2004. Potential for disease outbreaks continues to pose a major threat to the persistence of these isolated, endemic populations. We examined how roads influence the spatial ecology of San Clemente Island foxes (U. l. clementae), particularly in regard to spread of disease, to provide management recommendations for preventing or minimizing a disease outbreak on San Clemente Isla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Similarly, if pathogens are most likely to invade into low-density regions, vaccinating randomly throughout the area may be more effective. Previous studies have suggested that vaccination programs should also consider landscape features when designing deployment strategies: using natural barriers to enhance vaccination firewalls [73] and accounting for habitat corridors and roads that promote host movement [11,74]. Firewall vaccination would likely be most beneficial in situations where host populations living in and around key landscape features (such as narrow habitat corridors) could be saturated with vaccinations in order to more effectively reduced the number of hosts infected early in the epidemic and the risk of infection crossing the firewall.…”
Section: And S2 Table)mentioning
confidence: 99%
“…Similarly, if pathogens are most likely to invade into low-density regions, vaccinating randomly throughout the area may be more effective. Previous studies have suggested that vaccination programs should also consider landscape features when designing deployment strategies: using natural barriers to enhance vaccination firewalls [73] and accounting for habitat corridors and roads that promote host movement [11,74]. Firewall vaccination would likely be most beneficial in situations where host populations living in and around key landscape features (such as narrow habitat corridors) could be saturated with vaccinations in order to more effectively reduced the number of hosts infected early in the epidemic and the risk of infection crossing the firewall.…”
Section: And S2 Table)mentioning
confidence: 99%
“…For instance, investigations of the biogeography associated with rabies could detect factors that promote epidemic spread as well as barriers that prevent dissemination (Smith et al, 2002). Recent studies conducted with wildlife species have identified where vaccinations against rabies are more likely to be beneficial (Resnik et al, 2018). Because delayed interventions tend to be less effective and costlier, estimating when is the optimal (or critical response) time to intervene also requires geographical data (Rivas et al, 2003).…”
Section: Introductionmentioning
confidence: 99%